Recruitment consultants: a unique resource for job seekers - Mornet, Martin Pierre (2017)
The main purpose of this research is to highlight the value added by recruitment consultants to the recruitment process. The focus is oriented towards the relationship between recruitment consultants and job seekers, becoming candidates once they have applied to a job offer. After reviewing what the literature offers on this topic, we will conduct a qualitative research, including an exploratory study by interviewing two groups of six and seven people, representing both sides of the relationship. The findings of these interviews will show that several views are brought to this topic. It will mainly be understood that the relationship between a recruitment consultant and a candidate is quite different from the relationship a candidate and the potential employer would have. Interview responses will also examine the advantages job seekers have to use a recruitment agency in their job search.